PESAN KEMENTERIAN AGAMA DALAM MODERASI MELALUI MEDIA SOSIAL INSTAGRAM - Wuri Arenggoasih; Corona Raisa Wijayanti (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
Certainly, everyone knows diversity in Indonesia but everyone does not necessarily understand and respect it. Even though according to the rule of law, Indonesia guarantees freedom of religion, diversity of ethnic groups, languages and cultures. But in reality, the SARA dispute still continues to this day. Regrettably, SARA disputes make quarrels not only in real life but also on social media. As the most social media user, the sensitivity of SARA issues must be a joint vigilance. This was realized by the Ministry of Religion by raising the theme "Moderation for Diversity of the People". This theme became the foundation of the Ministry of Religion's work program and instruction to its shade institutions. Therefore, this study aims to find out communication messages in Islamic moderation by the Ministry of Religion through social media Instagram on the account @kemenag_ri as a driver of interaction. The research method used was content analysis at 286 posts (on 1 January to 17 September 2019). Through social media moderation concepts and content marketing RI 4.0 as a theoretical foundation, communication messages consisting of the driving force of interaction on @kemenag_ri (liking, commenting, hashtag and sharing) and content marketing as moderation powerful storytelling.